Overview of Total Cholesterol Levels in Prolanis Hypertensive Patients at the Kelapa Dua Community Health Center - Endah Cahya Nisa Anastasya; Syarah Anliza; Adipura atmadja Egok; Citra Trisna; Basil Okeahiam (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Hypertension is one of the non-communicable diseases whose prevalence continues to increase each year and contributes substantially to the risk of cardiovascular disease, especially when accompanied by high total cholesterol levels. This study aimed to describe total cholesterol levels among hypertensive patients participating in the Chronic Disease Management Program (Prolanis) at the Kelapa Dua Community Health Center, Tangerang Regency. This study used a descriptive design with a cross-sectional approach, and the sample consisted of 25 hypertensive Prolanis patients at the Kelapa Dua Community Health Center. Total cholesterol was examined using the CHOD-PAP method. The results showed that borderline-high total cholesterol levels by age were most common in the middle-aged group (45-59 years), with 7 respondents (64%), while 4 respondents (80%) had high cholesterol levels. Based on sex, high total cholesterol levels were found in 10 female respondents (91%) and 1 male respondent (9%). Based on the classification of total cholesterol levels by hypertension category, high total cholesterol was most frequently found in grade 1 hypertension, with 5 respondents (63%), while borderline-high cholesterol was found in 3 respondents (33%).